Bubble temperature measurements on binary mixtures formed by cyclohexane at 94.7 kPa - Vittal Prasad T.E.; Suchil Kumar S.; Bhanu Pratap Goud M.; Anil Kumar P.; Srinivas A.; Subrahmanyeswara Reddy P.; Prasad D.H.L. (My University, 2025)
Bubble temperatures at 94.7 k Pa, over the entire composition range, are measured for eight binary mixtures formed by cyclohexane with 1,1,1-trichloroethane, 1,1,2,2-tetrachloroethane, epichlorohydrin, 1,2-dimethoxyethane, 1,4-dioxane, 2-picoline, N,N-dimethylformamide, and dimethylacetamide. A Swietoslawski-type ebulliometer was used for the measurements. The liquid-phase mole fraction versus temperature measurements were represented by the Wilson model.